Comparative Transcriptomics and Metabolites Analysis of Two Closely Related Euphorbia Species Reveal Environmental Adaptation Mechanism and Active Ingredients Difference - Zheng, Han; Yu, Mu-Yao; Han, Yang; Tai, Badalahu; Ni, Sheng-Fa; Ji, Rui-Feng; Pu, Chun-Juan; Chen, Kang; Li, Fu-Quan; Xiao, Hua; Shen, Ye; Zhou, Xiu-Teng; et al. (Frontiers in Plant Science, 2022)
Root of Euphorbia fischeriana and Euphorbia ebracteolata are recorded as source plant of traditional Chinese medicine ‘Langdu’, containing active ingredients with anticancer and anti-AIDS activity. However, the two species has specific patterns in the graphic distribution. Compared with E. ehracteolata, E. fischeriana distributes in higher latitude and lower temperature areas, might have experienced cold stress adaptation. To reveal the molecular mechanism of environmental adaptation, RNA-seq was performed towards the roots, stems and leaves of E. fischeriana and E. ehracteolata. 6830 pairs of putative orthologs between the two species were identified. Estimations of non-synonymous/synonymous substitution rate ratios for these orthologs indicated that 533 of the pairs may be under positive selection (Ka/Ks > 0.5). Functional enrichment analysis revealed that significant proportions of the orthologs were in the TCA cycle, fructose and mannose metabolism, starch and sucrose metabolism, fatty acid biosynthesis, and terpenoid biosynthesis providing insights into how the two closely related Euphorbia species adapted differentially to extreme environments. Consistent with the transcriptome, a higher content of soluble sugars and proline was obtained in E. fischeriana, reflecting the adaptation of plants to different environments. Additionally, 5 primary or secondary metabolites were screened as biomarkers to distinguish the two species. Determination of 4 diterpenoids was established and performed, showing jolkinolide B as a representative component in E. fischeriana, while ingenol endemic to E. ebracteolate. To better study population genetics, EST-SSR markers were generated and tested in 9 species of Euphorbia. 33 of the 68 pairs were screened out for producing clear fragments in at least four species, which will furthermore facilitate studies on the genetic improvement and phylogenetics of this rapidly adapting taxon. In this study, transcriptome and metabolome analysis revealed the evolution of genes related to cold stress tolerance, biosynthesis of TCA cycle, soluble sugars, fatty acids and amino acids, consistent with the molecular strategy that genotypes adapting to environment. The key active ingredients of the two species were quantitatively analyzed to reveal the difference of pharmacodynamic substance basis and molecular mechanism, providing insights into rational crude drug use.